The Optimism as Self-actualization Fulfillment in the Novel Pollyanna - Azni Rizka Anandari Antung; Siti Hafsah; Ulum Janah (Prologue: Journal on Language and Literature, 2021)
This research aims to analyze the role of optimism towards self-actualization fulfillment in the novel Pollyanna by Eleanor H.Porter. The objective of this research is to identify the reflection of optimism obtained. The theory used in this research is the Optimism approach and the Hierarchy of Needs by Abraham Maslow. This research uses the qualitative descriptive method in the analysis of the novel. The researcher found the reflection of optimism and the basic need obtain in order to fulfill self-actualization. There are categorized the existence, help, happiness, and joyfulness which as the optimism reflection that became impact in self-actualization fulfillment of the main character.